Structural Change and the Current Account The Case of Germany - Coricelli, Fabrizio (OECD Economics Department Working Papers, 2012)
Using empirical evidence from panel analysis of current account dynamics and of bilateral trade balances, the paper argues that the large German current account surplus during the 2000s can be explained by an increasing gap between productivity growth in manufacturing vis-à-vis services. Such a gap is due not only to improvements in the manufacturing sector but also to a significant slowdown of productivity growth in services. Therefore, despite the success in export markets, the German surplus may signal long-run weaknesses associated with constraints on service sector productivity growth and the inability of productivity growth in manufacturing to create positive spill-over effects on services. Persistence of barriers to liberalisation in services as well as the dominant type of technological progress in manufacturing, based on improving the efficiency of existing products, may partly explain these phenomena. A key factor behind these sectoral differences is the education system, which relies on highly specialised vocational schools, generating high returns for on the job training and creating incentives for efficiency gains in existing products and sectors. The paper concludes that there is room for comprehensive structural policies consistent with an equilibrium reduction in the current account surplus, accompanied by higher and more balanced growth